The minstrelsy of Scotland : 200 Scottish songs adapted to their traditional airs [Bladmuziek] - Moffat, Alfred (London: Augener, 1896)
"arranged for voice with pianoforte accompaniment and supplemented with historical notes by Alfred Moffat Bibliotheek Camille HuysmansGeschenk aangeboden door de Socialistische Groep Emile Vandervelde en het Belgisch Vakbondscentrum in Groot-Brittannië aan Camille Huysmans ter gelegenheid van zijn 70ste verjaardag, Londen, 26 mei 1941"